Hepatitis B Virus Infection Among Leprosy Patients: A Case for Polymorphisms Compromising Activation of the Lectin Pathway and Complement Receptors - Boldt, Angelica Beate Winter; Oliveira-Toré, Camila de Freitas; Kretzschmar, Gabriela Canalli; Weinschutz Mendes, Hellen; Stinghen, Sérvio Túlio; Andrade, Fabiana Antunes; Bumiller-Bini, Valéria; Gonçalves, Letícia Boslooper; Braga, Anna Carolina de Moraes; Stahlke, Ewalda von Rosen Seeling; Velavan, Thirumalaisamy P.; Thiel, Steffen; et al. (Frontiers in Immunology, 2021)
Thousands of leprosy patients not only suffer of physical deformities, but also either have or have had hepatitis B virus (HBV) coinfection. Polymorphisms of the complement system modulate susceptibility to leprosy, but genetic susceptibility to past or present HBV infection is unknown. We used sequencing and multiplex sequence-specific PCR to genotype 72 polymorphisms of seven genes (MBL2, FCN1, FCN2, FCN3, MASP1, MASP2, C3) encoding components of the lectin pathway, and two genes encoding complement receptors (CR1, VSIG4) in 190 patients, of which 74 were positive for HBsAg and/or anti-HBc (HBV+, 93.2% with a resolved infection) and 116 lepromatous patients, and 408 HBV- blood donors. In addition, we tested for levels of proteins of the lectin pathway. We found no difference between serum concentrations of mannan-binding lectin (MBL), MBL-associated serine proteins (MASP-1, MASP-2, MASP-3, MAp44), ficolin-3 (FCN-3), soluble complement receptor 1 (sCR1) and MBL mediated C4 activation, measured by ELISA or TRIFMA in up to 167 HBV+ and HBV- patients. Haplotypes lowering protein levels or encoding dysfunctional proteins increased susceptibility to HBV infection: MBL2*LYQC (OR=3.4, p=0.02), MASP1*AC_CC (OR=4.0, p=0.015) and MASP2*1C2-l (OR=5.4, p=0.03). Conversely, FCN1*3C2 haplotype, associated with higher gene expression, was protective (OR=0.56, P=0.033). Other haplotypes associated with HBV susceptibility were: MASP2*2B1-i (OR=19.25, P=0.003), CR1*3A (OR=2.65, P=0.011) and VSIG4*TGGRCG (OR=12.55, P=0.014). Some polymorphisms in ficolin genes associated with lower protein levels increased susceptibility to leprosy/ HBV infection: FCN*1 (OR=1.66, P=0.029), FCN2*GGGCAC (OR=6.73, P=0.008), and FCN3*del_del_C (OR=12.54, P=0.037), and to lepromatous disease/ HBV infection: FCN2*TA (OR=2.5, P=0.009), whereas FCN2*MAG was associated with increased FCN-2 expression and resistance against coinfection (OR=0.29, P=0.026). These associations were independent of demographic factors and did not increase susceptibility to leprosy per se, except MASP2*1C2-l. Associations for FCN2, FCN3, MASP1, MASP2, and VSIG4 variants were also independent of each other. In conclusion, polymorphisms compromising activation of the lectin pathway of complement increase susceptibility to HBV infection, with ficolin polymorphisms playing a major role in modulating the susceptibility among leprosy patients.